The Profound Bond as A Bedrock of Quality Education: Exploring Al-Ghazali's Perception of Love between Teachers and Students - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Idriss, Ibrahim Dahiru (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This paper aims to examine the importance of a loving bond between teachers and students within the Islamic education system, particularly through the lens of Imam Al-Ghazali’s perceptions. The study employs a qualitative method, utilizing content analysis of relevant literature, primarily historical sources from the Islamic world, to interpret the concepts, ethics, and roles of teachers and students according to Al-Ghazali. The findings indicate that Al-Ghazali’s theory on the spirit of love between educators and learners offers crucial guidance on student support and nurturing. By emphasizing the development of a strong affectionate bond, educators can foster an environment conducive to learning and growth. The application of this concept is advised for contemporary educators, urging them to consciously promote a respectful and understanding teacher-student connection. The study's main contribution is providing fresh insights, integrating emotional, psychological, and and cognitive viewpoints, on how affection can significantly enhance the quality of instruction in the twenty-first century. Thus, the research concludes that Al-Ghazali’s conception of love is a critical bedrock for quality education.